Vehicle speed detection using frame differencing for smart surveillance system - Hasliza, A. Rahim@Samsuddin (Institute of Electrical and Electronics of Engineering (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/